The insufficiency of corrent policies to foster cooperatives and labour companies against economic crisis in Spain - Rafael Chaves Ávila (AECOOP Escuela de Estudios Cooperativos, 2014)
This article examines policies to foster cooperatives and labour companies during this time of crisis, identifying the main existing and new tools of governments, assessing their scope and evaluating their effectiveness. It identifies three policy groups: traditional promotion policies, new policies (including those devised by the regional governments and the new social economy law) and austerity policies. The first conclusion is that cooperatives and labour companies are not a highlysubsidised sector, as the scope of these policies has been very limited. The second, unexpectedly for a period of crisis, is that neither traditional mechanisms nor recently-devised ones have been deployed to a greater extent in recent years to combat unemployment and strengthen the social economy sector. Instead, the austerity measures have hit social economy policies badly by making severe cuts in their budget allocation.